Study on the applicability of ISO 14000 to Singapore construction industry - Low, Shuey Ming. (2008)
The main objective of this dissertation is to evaluate and explore the current practices of firms who have achieved and/or are achieving the ISO 14000 Environmental Management System (EMS) in the Singapore construction industry.